2017
DOI: 10.1002/ajcp.12213
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Intimacy, Mental Illness, and Homelessness

Abstract: The current article reviews the literature on sexuality among individuals with a severe mental illness (SMI) who have experienced homelessness, a topic that has received little attention in the research literature, particularly from a community psychology perspective. The review begins with a synthesis of the literature on SMI and sexuality, followed by a review of the available literature on SMI, homelessness, and sexuality. It concludes with an interpretation of the findings using community psychology values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…As it appears, these two conditions reinforce each other in severity in a vicious cycle. In addition, the specific substance, route of administration, and dosage are some of the key factors that affect the tendency of individuals to engage in high-risk sexual behaviours [32] while using methadone, as a replacement for opioid addiction, changes the method of substance abuse for the better with lower health risks [6,13]. However, it is particularly challenging to limit high-risk sexual behaviours in light of frequent anal sex (especially after using amphetamines), low self-esteem, lack of assertiveness, bad decision making skills, inefficient communication skills, low level of education and a history of mental disorders (in up to 45% of cases) [16,19,33].…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As it appears, these two conditions reinforce each other in severity in a vicious cycle. In addition, the specific substance, route of administration, and dosage are some of the key factors that affect the tendency of individuals to engage in high-risk sexual behaviours [32] while using methadone, as a replacement for opioid addiction, changes the method of substance abuse for the better with lower health risks [6,13]. However, it is particularly challenging to limit high-risk sexual behaviours in light of frequent anal sex (especially after using amphetamines), low self-esteem, lack of assertiveness, bad decision making skills, inefficient communication skills, low level of education and a history of mental disorders (in up to 45% of cases) [16,19,33].…”
Section: ■ Discussionmentioning
confidence: 99%
“…Among the homeless youth, prostitution is overrepresented by boys [12]. The desire for intimacy and the sense of social isolation are some of the reasons for prostitution among homeless men often associated with emotional, financial, and physical hazards [13]. However, some studies have also demonstrated that involvement in sexual behaviours for the purpose of earning money or obtaining drugs are closely correlated with a lack of shelter [6].…”
Section: ■ Introductionmentioning
confidence: 99%
“…The final group of articles included in the special issue highlights new and emerging, or under‐examined areas of community mental health that inform research and practice agendas for community psychologists in the years to come. First, Ecker, Cherner, Rae and Czechowski () review the literature on sexuality among individuals with serious mental illness who have experienced homelessness. This topic has received very little attention in the research literature, and findings from their review highlight the importance of intimate relationships to recovery and well‐being.…”
Section: Overview Of Contributions To the Special Issuementioning
confidence: 99%
“…Hopper (2012) issued a caution against the use of housing as a means of warehousing persons experiencing homelessness, a process antithetical to the right of every human being to realize his or her potential -- this caution underlines the relevance of focusing on and promoting thriving. Emerging research with formerly homeless persons in community psychology has begun to address this concern by emphasizing the importance of psychological integration (Ecker & Aubry, 2016), sexual and romantic intimacy (Ecker, Cherner, Rae & Czechowski, 2017), and centering client voices (Pruitt et al, 2018), though the concept of “thriving” has yet to gain significant traction in the published literature with this population. Recent findings that compassion for persons experiencing homelessness have increased among the public in the past two decades (Tsai et al, 2017) suggest that efforts to promote thriving and greater life fulfillment among formerly homeless persons may now be met with improved understanding and acceptance.…”
Section: Introductionmentioning
confidence: 99%